Frequency of Positive Surgical Margin at Prostatectomy and Its Effect on Patient Outcome. (9th May 2011) - Iczkowski, Kenneth A.; Lucia, M. Scott
Abstract : A positive surgical margin at prostatectomy is defined as tumor cells touching the inked edge of the specimen. This finding is reported in 8.8% to 42% of cases (median about 20%) in various studies. It is one of the main determinants of eventual biochemical (PSA) failure, generally associated with a doubled or tripled risk of failure. The effect of a positive margin on outcome can be modified by stage or grade and the length, number and location of positive margins, as well as by technical operative approach and duration of operator experience. This paper tabulates data from the past decade of studies on margin status.